x
2
+
y
2
=
3
8
9
x
y
=
1
7
0
find
∣
x
−
y
∣
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 + y 2 + 2 x y = 3 4 0 + 3 8 9
( x + y ) 2 = 7 2 9
( x + y ) = 2 7
1 7 × 1 0 = 1 7 0 → ∣ x − y ∣ = 7
Given that x 2 + y 2 = 3 8 9 and x y = 1 7 0
We can expand it to x 2 + y 2 − 2 x y = 3 8 9 − 2 ( 1 4 0 )
( x − y ) 2 = 4 9 or simply ∣ x − y ∣ = 7
We can write x^2+y^2 as (x-y)^2+2xy
By substituting the given values, we get
389=(x-y)^2+2(170)
=>389=(x-y)^2+340
=>389-340=(x-y)^2
=>49=>(x-y)^2
=>x-y=49^1/2
=>x-y=7
therefore x-y=7
x^2+y^2 = 389 = (x-y)^2 + 2xy.
xy=170.
thus, (x-y)^2 + 340 = 389.
implies, (x-y)^2 = 49.
thus, (x-y) = 7.
Subtracting twice the second expression from the first, we have
x 2 + y 2 − 2 x y = ( x − y ) 2 = 4 9
from where it follows that ∣ x − y ∣ = 7
2(x-y)=x^2+y^2,thus (x-y)2(170)=(x^2+y^2)=389,x-y(340)=x^2+y^2(389)equal to 389-340=49, mean that x-y= square root 49=x-y=7
Problem Loading...
Note Loading...
Set Loading...